Impact of foliar applied nano-urea on growth, productivity and profitability of hybrid rice (Oryza sativa L.) - Namasharma, Sreeja; Pahari, Aditi; Banik, Abhisek; Pal, Subhajit; Sana, Megha; Pal, Sukanta; Banerjee, Hirak (ORYZA-An International Journal of Rice, 2023)
In lowland rice cultivation, the application of conventional urea fertilizer provides low N to rice plants and exhibits low N use efficiency ( 30%) due to greater loss of N. Hence the present study hypothesized that nano-urea spray could fulfil N requirement of rice plants and thereby produce high yields. So, a field experiment was conducted on hybrid rice (cv. Arize-6444 Gold) at Regional Research Sub-Station, BCKV, Chakdaha, Nadia under new alluvial zone (NAZ) of West Bengal during winter (rabi) season of 2021-22 to assess the effect of nano-urea on growth attributes, yield components, yield, nutrient uptake and economics of hybrid rice.The experiment was laid out in randomized complete block design with six treatments [T1:100% RDN i.e. 150 kg ha-1 through urea, T2:100% N(Urea) + 2 foliar spray of nano-urea, T3:75% N (Urea) + 2 foliar spray of nano-urea, T4:50% N(Urea) + 2 foliar spray of nano-urea, T5:125% N (Urea) + 2 foliar spray of nano-urea, T6:Control], each replicated four times. All the treatments were consisted of a uniform recommended dose of 100% P and K (each of 80 kg ha-1) supplied through SSP and MOP, respectively, except for T6 (control). In each treatment, foliar spray was done with IFFCO nano-urea @ 4ml litre-1 of water twice at active tillering stage and panicle initiation stage. Results of the present experiment revealed that growth parameters of tested hybrid rice namely plant height, LAI, dry matter accumulation and crop growth rate registered better result under treatment T2 than other treatments. As expected, the above-mentioned growth attributes were lowest on receiving T6 treatment at almost all dates of observation. Among yield attributes of hybrid rice, number of panicles m-2(392), panicle length (32.46 cm) and panicle weight (5.58 g) were highest with treatment T5, while filled grains panicle-1(194) and 1000-grain weight (24.18 g) were maximum for T2 treatment. Highest grain yield (7.15 t ha-1) and HI (50.71%) of hybrid rice were obtained with T2 treatment, while the highest straw yield (7.20 t ha-1) was obtained with T5 treatment. The treatment T2 resulted in highest grain N (1.48%) and K (0.21%) content. Total cost of cultivation was highest in T5 (Rs. 77712 ha-1), but net return (Rs. 43720 ha-1) as well as B:C ratio (1.57) was highest for T2 treatment. Hence, the application of 100% RDN in conjunction with nano-urea spray twice at 25 and 50 DAT has been effective for higher productivity and profitability of hybrid rice cultivation.